Tinjauan Hukum Islam terhadap Praktek Kafa’ah sebagai Upaya Membentuk Keluarga Sakinah (Studi Praktek Kafa’ah di Kalangan Yayasan Pondok Pesantren Sunan Drajat) - R. Zainul Mushthofa; Siti Aminah (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2020)
One of the problems related to marriage is the issue of kafa'ah, namely alignment, equality, equivalence, or equality between the prospective husband and wife. One of the goals of kafa'ah is to realize the purpose of marriage, which is to create a happy family. In Islam, women are married for four reasons, because of her wealth, her offspring, her beauty and because of the power of her religion. Among these four factors, Islam emphasizes the choice of religion. The priority of Islam on religious factors in regulating this issue, of course, cannot be separated from efforts to achieve benefit, so the determination of kafa'ah is certainly in order to support this goal. This research is a field research that is research with data obtained from field activities. The research location is in the Sunan Drajat Islamic Boarding School, Banjaranyar village, Paciran district, Lamongan district. The results of the research conducted are that the pesantren community really understands the issue of kafa'ah, because the pesantren community is very knowledgeable about religious knowledge, it can be seen from their respective backgrounds that they are teachers at the Sunan Drajat Islamic Boarding School. In practice, among the Sunan Drajat Islamic boarding schools themselves, not all people in the pesantren scope apply kafa'ah in their marriages, but there are still those who apply kafa'ah both from the ndalem family and families living around the pesantren, even though from all criteria Kafa'ah is not applied, only a few, it is enough to be capital to build a household into a sakinah family